Differences in Root Resorption between Root Canal treated and contralateral vital tooth during Orthodontic Tooth Movement: A Systematic Review - Yang, Liu; Tiwari, Sanjay Kumar; Peng, Li (Orthodontic Journal of Nepal, 2016)
It is believed that root canal treated tooth apex goes under more resorption than contralateral vital tooth during orthodontic movement. The concept is still contradictory and therefore the aim of this systematic review was to search the evidence regarding this issue. The clinical trials performed on human subjects with vital and contralateral root canal treated tooth were included in the study. The evidence was searched in PubMed, EMBASE, Medline, Cochrane and Scopus. No language barrier was imposed. From analysis it found that there was no difference in amount of root resorption between vital and contralateral tooth. But, degree of resorption was determined by the intensity of force applied, force application technique (continuous or interrupted), duration of force application and direction of force application. Form the above fact it can be concluded that root canal treated tooth can be moved equal distance as vital contralateral tooth. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.41-44